Implementation of TOGAF ADM in Designing Enterprise Architecture for Netflix Company - Alisyahbana, Andi Naila Quin Azisah; Azis, Fajriani; Rini Cahyani Ramli; Febriyanti Gian Matthew; Vaneza Zefanya (Indonesian Journal of Enterprise Architecture, 2024)
Netflix is a digital media streaming service provider, where business Mainly, it is a subscription streaming service that provides films and television programs, including several programs created by Netflix itself. In building a good business process and implementing the running of a system, it takes a business architecture design, using a framework architecture to minimize errors that will occur in creating a framework. EA design is needed by the Netflix company in order to help and increase efficiency regarding enterprise architecture to improve company performance and even help companies to plan and manage system changes for the company. In designing this Enterprise Architecture, a method is used, namely TOGAF ADM which consists of 10 phases. But this research is limited to 4 phases, namely, Preliminary phase, Vision architecture, Business architecture and Information system architecture.